Implementation of the STEAM-Ethnosains Carita-based science learning model to enhance the creativity and critical thinking of primary school students - Desyi Rosita; Sigit Prasetyo; Sintha Sih Dewanti; Sangkot Sirait (Universitas Islam Negeri Walisongo Semarang in collaboration with PD PGMI Indonesia, 2026)
This research employed a descriptive qualitative approach to explore the implementation of the STEAM–Ethnoscience Carita-based science learning model in a primary school classroom to enhance students’ creativity and critical thinking skills. Data were collected through participatory observation, semi-structured interviews, and documentation, involving teachers, students, school leaders, and local community members. Student creativity and critical thinking development were identified through classroom observations, learning artifacts, and thematic analysis of learning activities during the implementation of the model. The findings indicate that integrating STEAM principles with local ethnoscience knowledge, particularly traditional agricultural practices, water management, and environmental conservation in the Carita community, significantly improved the quality of science learning. Contextual learning activities encouraged active student engagement, strengthened conceptual understanding, and fostered environmental awareness. The results also show a substantial improvement in students’ creativity and critical thinking abilities during the learning process, as reflected in their ability to generate ideas, analyze problems, and propose solutions during project-based activities. These findings demonstrate that the STEAM–Ethnoscience Carita model provides an effective pedagogical framework for developing 21st-century competencies in primary education and offers potential for adaptation in other educational contexts with similar cultural and ecological characteristics.